Gambaran Pengetahuan PHBS Siswa Kelas IV di SDN Wonomulyo 1 Kecamatan Poncokusumo - Wati, Annisha Rahma; Suharno, Budi; Lala, Handy (Poltekkes Kemenkes Malang, 2024)
Abstract Elementary school-age children are an age group that is vulnerable and susceptible to health problems, the more prominent problem is clean and healthy living behavior. PHBS (Clean and Healthy Living Behavior) is an effort to provide learning experiences to create conditions for individuals, families, groups and communities. The purpose of this study was to describe knowledge about clean and healthy living behavior for elementary school students. This research method is a quantitative method with a descriptive design that describes the description of the elementary school children's knowledge of how to live a clean and healthy life. Determination of the sample using purposive sampling with the number of respondents 30 grade 4 elementary school students. The results of the study showed that almost all respondents had good knowledge of 90% and a small proportion had sufficient knowledge of 10%. The conclusion is that almost all respondents never received information related to PHBS knowledge, but there were still some respondents who received information regarding PHBS with sources of information through teachers and the internet. Knowledge of SD Wonomulyo 1 students about Clean and Healthy Behavior (PHBS) after being educated using media print in the form of a leaflet that is in the good category, based on the results of statistical tests showing an overview of the knowledge of elementary school children about clean and healthy living behaviors. Keywords: School Children; Knowledge; Clean and Healthy Living Behavior (PHBS)